The role of resilience in diabetes stigma among young and middle‐aged patients with type 2 diabetes - Yi‐Bo Zhang; Zhen Yang; Hui‐Jun Zhang; Chao‐Qiang Xu; Tao Liu (Wiley, 2023)
Abstract Aim To explore the prevalence and related factors influencing diabetes stigma among Chinese young and middle‐aged patients with type 2 diabetes. Design A cross‐sectional, quantitative study was conducted through questionnaires. Methods A total of 453 young and middle‐aged patients with type 2 diabetes were recruited. Questionnaire survey was conducted with convenience sampling from September 2019 to December 2020. This included demographic questionnaire, Type 2 Diabetes Stigma Assessment Scale (DSAS‐2) and Connor-Davidson Resilience Scale (CD‐RISC). The STROBE checklist was applied as the reporting guideline for this study. Results The scores of diabetes stigma and resilience of patients were 48.18 ± 14.52 and 66.02 ± 7.18, respectively. Diabetes stigma was negatively correlated with resilience, the correlation coefficient was −0.581. The results showed that the complications, diabetes year, monthly income and insulin treatment are important factors affecting stigma. In addition, it is resilience that was a protective factor of diabetes stigma, explaining 27.2% of the variance in diabetes stigma.